The crisis of modernity - Del Noce, Augusto, 1910-1989 (McGill-Queen's studies in the history of ideas, 2014)
In his native Italy Augusto Del Noce is regarded as one of the preeminent political thinkers and philosophers of the period after the Second World War. The Crisis of Modernity makes available for the first time in English a selection of Del Noce's essays and lectures on the cultural history of the twentieth century. Del Noce maintained that twentieth-century history must be understood specifically as a philosophical history, because Western culture was profoundly affected by the major philosophies of the previous century such as idealism, Marxism, and positivism. Such philosophies became the secular, neo-gnostic surrogate of Christianity for the European educated classes after the French Revolution, and the next century put them to the practical test, bringing to light their ultimate and necessary consequences. One of the first thinkers to recognize the failure of Marxism, Del Noce posited that this failure set the stage for a new secular, technocratic society that had taken up Marx's historical materialism and atheism while rejecting his revolutionary doctrine. Displaying Del Noce's rare ability to reconstruct intellectual genealogies and to expose the deep metaphysical premises of social and political movements, The Crisis of Modernity presents an original reading of secularization, scientism, the sexual revolution, and the history of modern Western culture.